Cellulose-kaolin-rice hull powder composite modified material as well as preparation method and application thereof
By developing cellulose-kaolin-rice husk powder composite modified materials, using their porous and layered structures, the problem of low efficiency of lead-polluted water treatment in the prior art has been solved, and efficient, economical and environmentally friendly lead ion adsorption effect has been achieved. .
Patent Information
- Application Number
- CN202411716820.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems with low adsorption capacity and treatment efficiency in removing lead-contaminated water, especially when treatment of high concentrations of lead-contaminated water, it significantly affects treatment efficiency.
By developing a composite modified material of cellulose-kaolin-rice husk powder, the porous structure and layered structure of modified cellulose, modified rice husk powder and kaolin can achieve electrostatic adsorption and complex coordination of lead ions. Surface adsorption, pore filling and co-adsorption.
It significantly improves the adsorption capacity, adsorption rate and adsorption stability of lead ions, achieving more efficient lead pollution control, while both economical and environmentally friendly.
Smart Images

Figure HDA0005157062890000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water purification materials, and in particular to a cellulose-kaolin-rice husk powder composite modified material and a preparation method and application thereof. Background Art
[0002] Lead ions are a common environmental pollutant that poses serious hazards to human health and ecosystems. Lead poisoning can lead to problems such as damage to the nervous system, decreased intelligence, and developmental delays, especially in children. In addition, lead may also cause high blood pressure, kidney damage, and reproductive problems. The cumulative nature of lead puts people at higher risk for long-term exposure, and it is difficult to degrade in the environment. It persists in soil and water for a long time, further affecting the food chain.
[0003] In order to deal with lead pollution, the development of lead removal materials has gradually attracted attention. Among them, kaolin has a large specific surface area and rich pore structure, which can effectively adsorb lead ions; as a natural material, kaolin will not cause secondary pollution to the environment and is very suitable for eco-friendly water treatment, so it is regarded as a potential solution for removing lead ions. However, the lead ion adsorption capacity of natural kaolin is low, and a larger dose may be required to achieve the desired effect. In addition, the adsorption reaction rate is slow and it usually takes a long time to reach equilibrium, which significantly affects the treatment efficiency when treating high-concentration lead-contaminated water. In addition, as a natural material, cellulose has advantages such as renewability and environmental protection in removing lead ions, but it also faces challenges such as low adsorption capacity and treatment efficiency.
[0004] Therefore, it is necessary to combine modification technology and develop composite modified materials to improve the lead ion adsorption capacity and treatment efficiency in order to achieve more efficient lead pollution control. Summary of the invention
[0005] According to the first aspect of the present invention, a cellulose-kaolin-rice husk powder composite modified material is provided, wherein the raw material composition comprises: modified cellulose, modified rice husk powder and kaolin, wherein the mass ratio of the modified cellulose, the modified rice husk powder and the kaolin is 1:0.3:(0.25-0.75).
[0006] In the cellulose-kaolin-rice husk powder composite modified material of the present invention, the modified rice husk powder and the modified cellulose have a porous structure, and the layered structure of kaolin has a large specific surface area. The introduction of kaolin into the modified cellulose-modified rice husk powder composite system can fill the micropores and increase the specific surface area of the material as a whole, thereby increasing the number of adsorption active sites. The pore structure between the porous modified rice husk powder and kaolin can form a continuous adsorption channel, making it easier for lead ions to diffuse to the adsorption sites, thereby improving the adsorption rate and adsorption amount.
[0007] The cellulose-kaolin-rice husk powder composite modified material of the present invention synergistically removes lead ions in water through multiple mechanisms such as electrostatic adsorption, complex coordination, surface adsorption, pore filling and synergistic adsorption. First, the carboxyl and hydroxyl groups on the surface of modified cellulose and modified rice husk powder are negatively charged, which produce electrostatic adsorption effects on positively charged lead ions, and the negatively charged surface of kaolin further enhances this effect. Secondly, the carboxyl groups on the modified cellulose and modified rice husk powder form complex or coordination bonds with lead ions, which improves the stability of adsorption. In addition, the active sites and porous structure on the surface of the material provide abundant physical adsorption sites, so that lead ions are quickly adsorbed on the surface of the material and diffuse into the internal pores, further increasing the adsorption amount. Through the synergistic effect of these three materials, the composite modified material can show excellent lead ion adsorption capacity and adsorption stability in water treatment.
[0008] In some embodiments, the method for preparing modified cellulose comprises the following steps:
[0009] dissolving cellulose powder in a sodium hydroxide aqueous solution to obtain a cellulose solution;
[0010] The obtained cellulose solution is stirred at 40-70°C with a rotation speed of 400-600rpm, and then chloroacetic acid is added to react for 5-8 hours. After the reaction is completed, the pH value of the solution is adjusted to 4.0-5.0, and then the solution is ultrasonically treated for 10-50 minutes, and then centrifuged and washed, the precipitate is collected, and finally the precipitate is dried to obtain.
[0011] When preparing the modified cellulose, the present invention mainly introduces carboxymethyl (-CH2COOH) functional groups into the cellulose molecular chain through the carboxymethylation reaction of chloroacetic acid, thereby improving the adsorption capacity of cellulose for lead ions.
[0012] First, cellulose molecules are dissolved and activated: After cellulose is dissolved in sodium hydroxide aqueous solution, the hydrogen bonds of cellulose are partially broken, exposing more hydroxyl groups (-OH). Alkaline conditions ionize the hydroxyl groups of cellulose to form cellulose sodium salt (CO-Na+), thereby increasing the reactivity of cellulose.
[0013] Secondly, carboxymethylation reaction: During the reaction, chloroacetic acid undergoes a nucleophilic substitution reaction with the hydroxyl group in cellulose sodium salt, and the chlorine atom in chloroacetic acid is replaced by the hydroxyl group to generate a cellulose derivative containing a carboxymethyl (-CH2COOH) group.
[0014] Then, adjust the pH and ultrasonic treatment: After the reaction is completed, adjust the pH to 4.0-5.0 to neutralize the excess sodium hydroxide in the reaction system and stabilize the structure of carboxymethyl cellulose. Ultrasonic treatment further disperses the cellulose particles to prevent agglomeration, while enhancing the pore structure of the material and making the adsorption sites more evenly distributed.
[0015] The modified cellulose of the present invention can significantly improve the removal rate of lead ions because:
[0016] On the one hand, the introduction of carboxymethyl (-CH2COOH) groups enhances electrostatic adsorption: carboxymethyl (-CH2COOH) functional groups are introduced on the surface of the modified cellulose, and these groups will dissociate in water to generate negative charges (-COO-). 2 +) is positively charged, and electrostatically attracts the negative charge on the surface of modified cellulose, thereby significantly enhancing the adsorption capacity of lead ions. Due to the increase in carboxyl density, the total number of adsorption sites of modified cellulose is significantly increased, thereby improving the adsorption efficiency.
[0017] On the other hand, carboxyl groups form complex coordination bonds with lead ions: carboxyl groups and lead ions can form stable chemical bonds through chelation or coordination, thereby increasing the specific adsorption of lead ions. This chemical adsorption method is stronger and more stable than electrostatic adsorption, especially when there are other competing ions in the water, it can show higher selectivity.
[0018] In addition, the intermolecular interaction is enhanced: the modified cellulose molecular chains are more active and can form multiple interactions with lead ions through hydrogen bonds, electrostatic forces and coordination effects. These synergistic effects together improve the capture efficiency of lead ions.
[0019] In some embodiments, the concentration of the sodium hydroxide aqueous solution is 0.5-2 mol / L.
[0020] In some embodiments, the ratio of the mass of cellulose powder to the volume of the sodium hydroxide aqueous solution is (1-5):500.
[0021] In some embodiments, the mass ratio of chloroacetic acid to cellulose powder is 1:(1-5).
[0022] In some embodiments, acetic acid is added after the reaction is completed to adjust the pH value of the solution to 4.0-5.0.
[0023] In some embodiments, the centrifugal speed is 3000-8000 r / min, each centrifugation is 3-5 minutes, and the centrifugation is performed 3-5 times.
[0024] In some embodiments, the precipitate is dried at 40-60°C for 6-9 hours.
[0025] In some embodiments, the method for preparing modified rice husk powder comprises the following steps:
[0026] The rice husk powder is washed with water, then the washed rice husk powder is immersed in an acetic acid solution and stirred for 2-4 hours, then the rice husk powder is washed with water, and finally the washed rice husk powder is dried to obtain the product.
[0027] The main purpose of soaking and stirring the rice husk powder in the acetic acid solution in the present invention is:
[0028] On the one hand, impurities and inorganic salts can be removed: the acidity of the acetic acid solution can dissolve some impurities in the rice husk (such as carbonates, metal salts, ash, etc.), reduce the interference of inorganic components, improve the purity of the rice husk powder, and effectively reduce the hydrophobic substances on the surface of the rice husk (such as wax and organic residues), exposing more adsorption active sites.
[0029] On the other hand, the surface activity of rice husk powder is improved: rice husk contains a large amount of silicates and other biomacromolecules. Acetic acid treatment can remove some weakly bound inorganic substances and surface passivation substances, making the hydroxyl groups and other functional groups on the rice husk surface more exposed, making the rice husk surface more hydrophilic and adsorbent. At the same time, the hydroxyl groups and other functional groups in the rice husk fiber will be partially activated in an acidic environment, providing more active sites for subsequent reactions.
[0030] The modified rice husk powder treated with acetic acid has higher purity, stronger hydrophilicity, larger specific surface area and more active sites, thereby significantly improving the adsorption efficiency of lead ions.
[0031] In some embodiments, the concentration of the acetic acid solution is 5-10% (V / V).
[0032] In some embodiments, the ratio of the mass of the rice husk powder to the volume of the acetic acid solution is (5-25):500.
[0033] In some embodiments, the stirring speed is 500-800 r / min.
[0034] In some embodiments, the washed rice husk powder is dried at 60-80° C. for 5-8 h.
[0035] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned cellulose-kaolin-rice husk powder composite modified material, comprising the following steps:
[0036] The modified cellulose, modified rice husk powder and kaolin are mixed according to a proportion to obtain a mixed powder, and then the mixed powder is ground into a powder with a particle size of 1-3 μm.
[0037] According to a third aspect of the present invention, there is provided a use of the above-mentioned cellulose-kaolin-rice husk powder composite modified material in the preparation of a lead ion adsorption passivation material.
[0038] The beneficial effects of the present invention include:
[0039] (1) The cellulose-kaolin-rice husk powder composite modified material provided by the present invention has a high efficiency of lead ion adsorption capacity. After the carboxymethylation reaction, a large number of carboxyl groups are successfully introduced into the cellulose, which enhances the complexing ability with lead ions and improves the adsorption performance of cellulose, so that it shows stronger adsorption capacity, rate and stability when removing lead ions; the rich pores and large specific surface area of kaolin provide more space for the adsorption of lead ions. Kaolin itself has high adsorption and good chemical stability, and the adsorption performance of the whole material can be enhanced after the composite; rice husk powder is rich in cellulose and lignin, has a large specific surface area and rich pore structure, and the rice husk powder treated with acetic acid has higher purity, stronger hydrophilicity, larger specific surface area and more active sites, so that it can more effectively adsorb lead ions. The carboxylated modified cellulose and the rice husk powder treated with acetic acid complement each other with kaolin in terms of specific surface area, pore structure, surface functional groups, etc., increase the overall adsorption capacity of the material, and the combination of the three achieves a synergistic effect, which significantly improves the removal rate and removal efficiency of lead ions.
[0040] (2) The cellulose-kaolin-rice husk powder composite modified material provided by the present invention is both economical and environmentally friendly. Cellulose, rice husk powder and kaolin are all widely available natural resources with low prices and significant cost advantages. Cellulose comes from plants and has good biocompatibility, while kaolin is a natural mineral, which means that the composite material will not introduce secondary pollution during water treatment. In addition, rice husk is an agricultural byproduct with low cost and easy to obtain. The use of rice husk powder can reduce the overall production cost of the composite modified material, which has economic advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The figure is a graph showing the change of lead ion removal rate over time for the test samples of Example 1 and Comparative Examples 1-2 and 4. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the accompanying drawings. It is worth noting that the following examples are only for better explanation of the content of the present invention and are not intended to limit the scope of protection of the present invention. The undisclosed process steps in the examples are prior art. Unless otherwise specified, the following raw materials are commercially available.
[0043] Example 1
[0044] The preparation method of the cellulose-kaolin-rice husk powder composite modified material of this embodiment comprises the following steps:
[0045] (1) 4 g of cellulose powder (particle size ≤ 20 μm) was dissolved in 500 mL of a 1 mol / L sodium hydroxide aqueous solution to obtain a cellulose solution.
[0046] (2) The cellulose solution obtained in step (1) is stirred at 60° C. and a speed of 500 rpm, and then 1 g of chloroacetic acid is added to the above solution and reacted for 6 hours. After the reaction is completed, acetic acid is added to the obtained solution until the pH value of the solution reaches 5.0, and then the solution is ultrasonically treated for 30 minutes, and then centrifuged for washing at a centrifugal speed of 5000 r / min, each centrifugation for 4 minutes, centrifuged 3 times, and the precipitate is collected, and then the precipitate is dried at 60° C. for 8 hours to obtain modified cellulose.
[0047] (3) 10 g of rice husk powder was washed with deionized water to remove impurities and dust, and then the washed rice husk powder was immersed in 500 mL of 10% (V / V) acetic acid solution and stirred for 2 hours at a speed of 600 rpm. The rice husk powder was then washed with deionized water by suction filtration, and finally the washed rice husk powder was dried at 70° C. for 6 hours to obtain modified rice husk powder.
[0048] (4) The modified cellulose obtained in step (2), the modified rice husk powder obtained in step (3) and kaolin are mixed in a mass ratio of 1:0.3:0.45 to obtain a mixed powder, and then the mixed powder is finely ground into a powder with a particle size of about 1.5 μm using a ball mill to obtain a cellulose-kaolin-rice husk powder composite modified material.
[0049] Comparative Example 1
[0050] The preparation method of the composite modified material of this comparative example is substantially the same as that of Example 1, except that the modified rice husk powder and kaolin are not added in this comparative example.
[0051] Comparative Example 2
[0052] The preparation method of the composite modified material of this comparative example is substantially the same as that of Example 1, except that kaolin is not added in this comparative example.
[0053] Comparative Example 3
[0054] The preparation method of the composite modified material of this comparative example is substantially the same as that of Example 1, except that no modified rice husk powder is added in this comparative example.
[0055] Comparative Example 4
[0056] In this comparative example, the cellulose powder, rice husk powder and kaolin are not modified. The cellulose powder, rice husk powder and kaolin are directly mixed in a mass ratio of 1:0.3:0.45 to obtain a mixed powder, and then the mixed powder is finely ground into a powder with a particle size of about 1.5 μm using a ball mill.
[0057] Next, in order to verify the adsorption capacity of the cellulose-kaolin-rice husk powder composite modified material prepared by the present invention on lead ions in wastewater, lead ion adsorption tests were carried out on the composite materials prepared in Example 1 and Comparative Examples 1-4.
[0058] 1. Test subjects
[0059] Composite materials prepared in Example 1 and Comparative Examples 1-4.
[0060] 2. Test methods
[0061] Taking industrial wastewater as the waste liquid to be treated, the concentration of lead ions in the waste liquid to be treated was detected by inductively coupled plasma mass spectrometry and was 0.83 mg / L.
[0062] Take 0.2g of the composite material test samples prepared in Example 1 and Comparative Examples 1-4 respectively and place them in 200mL of the waste liquid to be treated, adjust the pH to 6.0, and stir at 500r / min at room temperature for 20, 40, 60, and 80min respectively. After solid-liquid separation, detect the concentration of lead ions in the solution, calculate the lead ion removal rate and make a record. Each sample is tested 3 times and the average value is taken. Lead ion removal rate (%) = (c i -c f ) / c i × 100%, where c i is the initial concentration of lead ions, in mg / L; c f It is the concentration of lead ions after adsorption, in mg / L.
[0063] 3. Test results
[0064] The change curves of lead ion removal rate of the test samples of Example 1 and Comparative Examples 1-2 and 4 over time are as follows: Figure 1 The lead ion removal rate of each test sample after 80 minutes of adsorption is shown in Table 1.
[0065] Table 1 Lead ion removal rate of each test sample after 80 minutes of adsorption
[0066] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Lead ion removal rate / % 99.5 88.9 91.7 92.8 83.1
[0067] From Table 1 and Figure 1It can be seen from the results that the adsorption rate of the test sample is the fastest within 0-20 minutes, and then the adsorption rate gradually slows down, reaching the maximum adsorption capacity in 80 minutes. The lead ion removal rate of the cellulose-kaolin-rice husk powder composite modified material prepared in Example 1 for industrial wastewater is 99.5%, close to 100%, showing very excellent lead ion adsorption performance; while the lead ion removal rate of the composite modified materials of Comparative Examples 1-3 for industrial wastewater is only about 90%, and the lead ion removal rate of the composite material of Comparative Example 4 for industrial wastewater is only 83.1%. It can be seen that the adsorption capacity of the cellulose-kaolin-rice husk powder composite modified material of the present invention for lead ions in industrial wastewater is stronger than that of the composite modified material without adding modified rice husk powder and kaolin or without adding kaolin or without adding modified rice husk powder, and is also stronger than the composite material without modifying the cellulose powder, rice husk powder and kaolin.
[0068] The above are only some specific embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A cellulose-kaolin-rice husk powder composite modified material, characterized in that: The raw material composition includes: modified cellulose, modified rice husk powder and kaolin, wherein the mass ratio of the modified cellulose, the modified rice husk powder and the kaolin is 1:0.3:(0.25-0.75).
2. The cellulose-kaolin-rice husk powder composite modified material according to claim 1, characterized in that: The preparation method of the modified cellulose comprises the following steps: dissolving cellulose powder in a sodium hydroxide aqueous solution to obtain a cellulose solution; The obtained cellulose solution is stirred at 40-70°C with a rotation speed of 400-600rpm, and then chloroacetic acid is added to react for 5-8 hours. After the reaction is completed, the pH value of the solution is adjusted to 4.0-5.0, and then the solution is ultrasonically treated for 10-50 minutes, and then centrifuged and washed, the precipitate is collected, and finally the precipitate is dried to obtain.
3. The cellulose-kaolin-rice husk powder composite modified material according to claim 2, characterized in that: The concentration of the sodium hydroxide aqueous solution is 0.5-2 mol / L; The ratio of the mass of the cellulose powder to the volume of the sodium hydroxide aqueous solution is (1-5):
500.
4. The cellulose-kaolin-rice husk powder composite modified material according to claim 2 or 3, characterized in that: The mass ratio of the chloroacetic acid to the cellulose powder is 1:(1-5); After the reaction is completed, acetic acid is added to adjust the pH value of the solution to 4.0-5.0; The centrifugal speed is 3000-8000r / min, each centrifugation is 3-5min, and the centrifugation is 3-5 times; The precipitate was dried at 40-60°C for 6-9 hours.
5. The cellulose-kaolin-rice husk powder composite modified material according to claim 1 or 2, characterized in that: The preparation method of the modified rice husk powder comprises the following steps: The rice husk powder is washed with water, then the washed rice husk powder is immersed in an acetic acid solution and stirred for 2-4 hours, then the rice husk powder is washed with water, and finally the washed rice husk powder is dried to obtain the product.
6. The cellulose-kaolin-rice husk powder composite modified material according to claim 5, characterized in that: The concentration of the acetic acid solution is 5-10%; The ratio of the mass of the rice husk powder to the volume of the acetic acid solution is (5-25):500; The stirring speed is 500-800r / min; The washed rice husk powder was dried at 60-80°C for 5-8h.
7. The method for preparing the cellulose-kaolin-rice husk powder composite modified material according to any one of claims 1 to 6, characterized in that: The steps include: The modified cellulose, modified rice husk powder and kaolin are mixed according to a proportion to obtain a mixed powder, and then the mixed powder is ground into a powder with a particle size of 1-3 μm.
8. Use of the cellulose-kaolin-rice husk powder composite modified material according to any one of claims 1 to 6 in the preparation of lead ion adsorption passivation materials.
Citation Information
Patent Citations
Medicament capable of removing activated carbon powder in wastewater
CN113023851A